(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The aquacultural potential (such as food and feeding habits) of a fish cannot be thoroughly determined without the knowledge of some aspects of its bioecology. This study investigated aspects of the bioecology of Tarpon, Megalops atlanticus (Valenciennes,1847) in Lagos Lagoon, Lagos, Nigeria. A total of 1,115 fish specimens from three (3) sampling stations A (Igbo Elejo -334), B (Tomaro - 448)) and C (Itan Agan- 333) were collected between January 2016 and April 2018. The study’s objectives included assessment of physico-chemical parameters, morphometric characters, food and feeding habits, and reproductive behaviours. Total length and body weight were measured with a standard measuring board and Sartorius weighing balance respectively. Growth patterns, condition factor, length frequency distribution, and gonadosomatic index (GSI) were determined using Standard scientific methods. Sexes were differentiated by both macro and microscopical examinations of the genitals. Feeding habits of the M. atlanticus were determined using frequency of occurrence and numerical methods. The gonadal stages were determined using histological examinations of the gonads. Water parameters (pH, dissolved oxygen, turbidity, salinity, CO2, temperature, total alkalinity, and total hardness) were measured following the American Public Health Association Standard.